Study of factors affecting the in vitro release of ketoprofen from carbomers-based gels - Bezugla, Olena; Liapunova, Anna; Zinchenko, Igor; Liapunov, Oleksii; Lyapunov, Nikolay; Stolper, Yurij (ScienceRise: Pharmaceutical Science, 2022)
The aim. To identify some factors affecting the in vitro release of ketoprofen from carbomer-based gels. Materials and methods. Carbomer-based gels containing ketoprofen as well as a Newtonian liquid without carbomer, which was the dispersion medium of the gel, were studied by rotational viscometry and spin probe method. The flow behaviour and rheological parameters were determined using the rheograms, and the rotational correlation times of the two dissolved spin probes, the molecules of which contain a carboxyl group or an amino group, were determined by EPR spectra. In vitro release tests were performed using vertical diffusion chambers using a validated method. The quantitative determination of ketoprofen in gels, liquid and receptor medium was performed by liquid chromatography, and ethanol was quantified by gas chromatography according to validated procedures. Gels with different brands of carbomers, neutralised with trolamine or trometamol, with different contents of ketoprofen and ethanol, and with pH from 6.0 to 7.0 were studied. Results. The sol → gel transition due to the neutralisation of the carbomer did not affect the shape and parameters of the EPR spectrum of the spin probe containing a carboxyl group in the molecule (like a carbomer and ketoprofen) in contrast to the probe with an amino group. If the substance dissolved in the gels does not interact with the carbomer, then its molecules/ions rotate rapidly in the liquid medium. This facilitates the release of a such substance from carbomer-based gels. The medicinal product Nobi Gel® gel 2.5 % and Newtonian liquid were equivalent in relation to the in vitro release parameters of ketoprofen from these objects. Сarbomer-based gels, which differed significantly in terms of rheological parameters, were also found to be equivalent in terms of ketoprofen release parameters. The in vitro release of ketoprofen was affected by its concentration and ethanol content in the gel. A change in pH from 6.0 to 7.0 practically did not affect the parameters of in vitro release of ketoprofen from gels. Conclusions. The formation of a carbomer-based gel did not affect the rotational correlation time of the probe, which did not interact with the carbomer. Parameters of in vitro release of ketoprofen from the gel and Newtonian liquid differed little; these parameters were also little affected by the difference in apparent viscosity of the gels. The in vitro release of ketoprofen depended on its concentration and ethanol content